2017
DOI: 10.1002/jcb.26189
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Protects Keratinocytes Against UVB Radiation‐Induced Carcinogenesis via Negative Regulation of FOXO3a Through the mTORC2/AKT Signaling Pathway

Abstract: Lycopene, one of the most potent anti-oxidants, has been reported to exhibit potent anti-proliferative properties in a wide range of cancer cells through modulation of the cell cycle and apoptosis. Forkhead box O3 (FOXO3a) plays a pivotal role in modulating the expression of genes involved in cell death. Herein, we investigated the role of FOXO3a signaling in the anti-cancer effects of lycopene. Results showed that lycopene pretreatment attenuated UVB-induced cell hyper-proliferation and promoted apoptosis, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 59 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Forkhead box O3a (FOXO3a), a highly evolutionarily conserved transcription factor, mediates numerous cellular processes, including cell proliferation, cell apoptosis, cell cycle and carcinogenesis [ 16 , 17 ]. p53 and FOXO3a could activate the pro-apoptotic PUMA protein (p53-upregulated modulator of apoptosis), resulting in cell apoptosis and cell cycle arrest [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Forkhead box O3a (FOXO3a), a highly evolutionarily conserved transcription factor, mediates numerous cellular processes, including cell proliferation, cell apoptosis, cell cycle and carcinogenesis [ 16 , 17 ]. p53 and FOXO3a could activate the pro-apoptotic PUMA protein (p53-upregulated modulator of apoptosis), resulting in cell apoptosis and cell cycle arrest [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with lycopene decreased UVB-caused cell proliferation while increasing apoptosis via declining CDK2 and CDK4 in hairless SKH-1 mice and human keratinocytes [82]. Moreover, the study conducted on volunteers revealed that lycopene decreased the expression of UVA1 radiation-inducible genes HO-1 upregulation caused by UVA1 and UVA/B [72].…”
Section: Against Dermatologic Diseasesmentioning
confidence: 95%
“…Furthermore, protein kinase B (AKT) loss can induce more lycopene-caused FOXO3a dephosphorylation, whereas losing the mechanistic target of rapamycin complex 2 (mTORC2) via transfection with a rapamycin-insensitive companion of mammalian target of rapamycin (RICTOR) siRNA induces AKT phosphorylation to amounts like the levels gained by lycopene. On the other hand, AKT/mTORC2 overexpression decreases the lycopene impact on the FOXO3a expression and AKT phosphorylation, indicating the link between lycopene and the mTORC2/AKT signaling negative modulation [82]. Interestingly, lycopene treatment for human breast carcinoma cell line MCF-7 in vitro, leading to cell shrinkage and breakage, is dependent on the dose and time.…”
Section: Cardioprotectivementioning
confidence: 99%
“…Therefore, we know that lycopene, which is the most abundant carotenoid in tomato, may enhance human health benefits in many systems. According to a previous dermatology study, lycopene protects human keratinocytes against full spectrum UVR damage [13]. Although the HaCaT cells immortal, the virtually normal degree of morphologic differentiation was further substantiated by the regular spatial distribution of epidermal differentiation products.…”
Section: Introductionmentioning
confidence: 92%